2011
DOI: 10.1111/j.1464-410x.2011.10126.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy: an underdiagnosed cause of erectile dysfunction

Abstract: OBJECTIVES • To assess the prevalence of peripheral neuropathy in patients with erectile dysfunction (ED). • To evaluate the reliability of clinical tests such as the five‐item version of the International Index of Erectile Function (IIEF‐5) and the Neuropathy Symptom Score (NSS) classification system in predicting the concurrence of peripheral neuropathy. PATIENTS AND METHODS • We studied 90 patients who were consecutively recruited from the Department of Andrology of the Central Hospital of Asturias. • Anamn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The latency of cortical P40>45ms or left–right difference >2.5ms were considered abnormal in PTSSEPs test. P40 latency>44.1 ms was considered pathological in PDEPs test ( 20 ). BCR test was performed by applying electrical pulses on the penis and the responses were recorded from both bulbocavernosus muscles with concentric needle electrodes ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latency of cortical P40>45ms or left–right difference >2.5ms were considered abnormal in PTSSEPs test. P40 latency>44.1 ms was considered pathological in PDEPs test ( 20 ). BCR test was performed by applying electrical pulses on the penis and the responses were recorded from both bulbocavernosus muscles with concentric needle electrodes ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…P40 latency>44.1 ms was considered pathological in PDEPs test ( 20 ). BCR test was performed by applying electrical pulses on the penis and the responses were recorded from both bulbocavernosus muscles with concentric needle electrodes ( 20 , 21 ). Abnormal results include absent responses, response latency >37ms and interside differences >1.5ms.…”
Section: Methodsmentioning
confidence: 99%
“…Organic, relational, and psychological factors contribute to ED and include neurogenic, vasculogenic, iatrogenic, and endocrine pathways, which mediate penile endothelial dysfunction and defective noradrenergic and cholinergic nerve signalling with increased cavernosal contractile sensitivity and impaired dilatory function . Vascular abnormalities including penile smooth muscle and endothelial dysfunction and altered cavernosal haemodynamics have been considered to play a major role in diabetes related ED, whilst the impact of neuropathy has been underestimated . Indeed, some studies have identified an association between cardiac autonomic and somatic neuropathy and ED and attributed failure of phosphodiesterase type‐5 (PDE5) inhibitor therapy in patients with ED to the presence of small fibre and autonomic neuropathy …”
Section: Introductionmentioning
confidence: 99%
“…10 Vascular abnormalities including penile smooth muscle and endothelial dysfunction and altered cavernosal haemodynamics have been considered to play a major role in diabetes related ED, 11 whilst the impact of neuropathy has been underestimated. 12 Indeed, some studies have identified an association between cardiac autonomic and somatic neuropathy and ED and attributed failure of phosphodiesterase type-5 (PDE5) inhibitor therapy in patients with ED to the presence of small fibre and autonomic neuropathy. [13][14][15] The contribution of neuropathy to ED has been assessed using symptoms, vibration perception and reflexes, 16 neurophysiology, 17,18 quantitative sensory testing (QST), and the sympathetic skin response (SSR).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in participants with type 1 diabetes from the DCCT and EDIC cohorts have also shown that cardiovascular autonomic neuropathy and peripheral neuropathy are major risk factors for erectile dysfunction [8, 9]. Furthermore, failure of erectile dysfunction therapy has been attributed to severe erectile dysfunction at presentation, worsening of endothelial dysfunction and the presence of a significant neuropathy [10, 11]. …”
Section: Introductionmentioning
confidence: 99%